2013
DOI: 10.1021/am4021236
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Contact at the Interface between Silicon and Transfer-Printed Gold Films by Eutectic Joining

Abstract: This paper presents the electrical and morphological properties at the interface between a metal (Au) and a semiconductor (Si) formed by a novel transfer-printing technology. This work shows that a transfer-printed thin (hundreds of nanometers) Au film forms excellent electrical contact on a Si substrate when appropriate thermal treatment is applied. The successful electrical contact is attributed to eutectic joining, which allows for the right amount of atomic level mass transport between Au and Si. The outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…2(c) ) as well as electrical conductance between Au – Au (Inset plot in Fig. 4(d) ) and Au-Si 29 strongly support the device level capabilities of the micro-Lego technique. While the experimentally obtained Q-factor and insertion loss from the microtoroid resonator and the RF MEMS switch presented in this work display their functionalities, they do not outperform their state of the art counterparts.…”
Section: Discussionsupporting
confidence: 53%
“…2(c) ) as well as electrical conductance between Au – Au (Inset plot in Fig. 4(d) ) and Au-Si 29 strongly support the device level capabilities of the micro-Lego technique. While the experimentally obtained Q-factor and insertion loss from the microtoroid resonator and the RF MEMS switch presented in this work display their functionalities, they do not outperform their state of the art counterparts.…”
Section: Discussionsupporting
confidence: 53%
“…Various such techniques include transfer printing, the trench-protect-release (TPER) based process, double transfer printing, soft-etch-back (SEB), corrugation architecture, silicon-on-insulator (SOI), and laser lift-off process. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The practical advantages of making materials flexible include ability to deploy on a complex and asymmetrical surfaces, enhancing device performance due to excellent and proven conventional superior properties matching with the current state-of-the-art rigid device technologies, in addition to reducing the form factor which implies low weight and low cost due to new and easy fabrication processes. [36,37] Any free-standing material that is less than 100 nm in one of its three spatial dimensions can be inherently flexible and is often termed a nanomaterial.…”
Section: Optimal Materials For Harsh Environmentsmentioning
confidence: 99%
“…Different ink materials may require different sacrificial layers to be prepared as inks. For example, an Si, SiO 2 , or polymethylmethacrylate (PMMA) sacrificial layer is necessary to make SiO 2 , Au, or SU8 ink, respectively [35,59,60,61,62]. However, for any ink materials, inks are photolithographically patterned with desired shapes and entail relatively low adhesion or joining to donor substrates.…”
Section: Ink Preparationmentioning
confidence: 99%
“…In order to use micro-LEGO-assembled structures within device applications, the electrical contact at the interface between two assembled materials, especially metal–semiconductor or metal–metal interfaces, should be acceptable. First, a transmission line model (TLM) [70,71,72] was adopted to measure the contact resistance of transfer-printed Au inks on Si (Figure 8a) and their ohmic contact characteristics were demonstrated [61]. It was observed that a transfer-printed Au ink on Si exhibits significantly reduced contact resistance when they are thermally processed at or above the bulk eutectic temperature.…”
Section: Joiningmentioning
confidence: 99%